Skrining Fitokimia dan Profil KLT Ekstrak dan Fraksi dari Daun Berenuk (Cresentia cujete L.) serta Uji DPPH: Phytochemical Screening and TLC Profile of Extracts and Fractions from Leaves of Berenuk (Cresentia cujete L.) and DPPH Test - Brigita Olivia Intan Kinam; Wisnu Cahyo Prabowo; Supriatno Supriatno; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Berenuk or Maja Leaves (Cresentia cujete L.) is a plant that grows in the tropics. In Indonesia, the use of Berenuk Leaves for health is not utilized optimally, and there is still a lack of research on this plant. To be able to be developed as a traditional medicinal ingredient, it is necessary to know the content of secondary metabolites contained in berenuk leaf extract. This study aims to determine the secondary metabolites contained in berenuk leaf extract through phytochemical screening, TLC profile in C. cujete L. leaves. Extraction was carried out using methanol by maceration. After fractionation were carried out by using n-hexane and ethyl acetate as solvents. Then, a phytochemical analysis was screened and a TLC bioautography. Secondary metabolites by the compounds contained in C. cujete L. are alkaloids, tannins, saponins and steroids. C. cujete L. which has antioxidant activity was marked with yellow spots on TLC plates that had been sprayed with DPPH.